2023
DOI: 10.1001/jama.2023.18497
|View full text |Cite
|
Sign up to set email alerts
|

Orthostatic Hypotension, Hypertension Treatment, and Cardiovascular Disease

Stephen P. Juraschek,
Jiun-Ruey Hu,
Jennifer L. Cluett
et al.

Abstract: ImportanceThere are ongoing concerns about the benefits of intensive vs standard blood pressure (BP) treatment among adults with orthostatic hypotension or standing hypotension.ObjectiveTo determine the effect of a lower BP treatment goal or active therapy vs a standard BP treatment goal or placebo on cardiovascular disease (CVD) or all-cause mortality in strata of baseline orthostatic hypotension or baseline standing hypotension.Data SourcesIndividual participant data meta-analysis based on a systematic revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 44 publications
2
7
0
Order By: Relevance
“…In Reply In response to the Letter by Drs Palma and Kaufmann about our recent study, we agree that patients must be treated individually and in the context of their specific conditions. Patients with true autonomic disorders and severe orthostatic hypotension, who are identified by the severity and reproducibility of their orthostatic hypotension, should be referred for specific management.…”
supporting
confidence: 76%
“…In Reply In response to the Letter by Drs Palma and Kaufmann about our recent study, we agree that patients must be treated individually and in the context of their specific conditions. Patients with true autonomic disorders and severe orthostatic hypotension, who are identified by the severity and reproducibility of their orthostatic hypotension, should be referred for specific management.…”
supporting
confidence: 76%
“…To the Editor A recent meta-analysis of randomized trials of pharmacologic treatment for high blood pressure (BP) reported that antihypertensive therapy reduced the risk of cardiovascular disease (CVD) and mortality similarly in patients with and without orthostatic hypotension. The authors therefore advocated for intensive antihypertensive treatment despite the presence of orthostatic hypotension.…”
mentioning
confidence: 99%
“…As noted by the authors, dizziness, syncope, and injurious falls were not considered as end points, so it is unclear whether hypotension-related events were more frequent in the low BP goal/active antihypertensive group. Also, some trials in this meta-analysis excluded patients with standing hypotension at baseline (ie, SPRINT). Patients with symptomatic orthostatic hypotension were also likely not included in this meta-analysis due to exclusion of participants unable to remain in the standing position (eg, HYVET), or those with “other cardiovascular disease, serious illness, or contraindication” (eg, AASK).…”
mentioning
confidence: 99%
“…In the Original Investigation titled “Orthostatic Hypotension, Hypertension Treatment, and Cardiovascular Disease: An Individual Participant Meta-Analysis,” published in the October 17, 2023, issue of JAMA , author Jan Staessen’s affiliations were incorrectly listed. The correct affiliations for Dr Staessen are the Research Association Alliance for the Promotion of Preventive Medicine, Mechelen, Belgium, and the Biomedical Research Group, Faculty of Medicine, University of Leuven, Leuven, Belgium.…”
mentioning
confidence: 99%